Formulation and Physicochemical Characterization of Guava (Psidiumguajava L.) Leaf Extract-Loaded Chitosan Nanoparticles - Winda Prasetya Rini; Yunahara Farida; Deni Rahmat (Jurnal Riset Kefarmasian Indonesia, 2026)
Guava (Psidium guajava L.) leaf extract is rich in secondary metabolites; however, its utilization as a therapeutic agent is frequently hindered by poor solubility and low bioavailability. The development of submicron-scale drug delivery systems, specifically chitosan nanoparticles, presents an approach to overcome these limitations. This study aimed to formulate and characterize chitosan nanoparticles loaded with guava leaf extract to fulfill the physicochemical stability parameters of a nanosuspension preparation. The extraction process was conducted using the maceration method with 96% ethanol. The nanoparticles were synthesized via the ionic gelation method using a 1% chitosan polymer and sodium tripolyphosphate (NaTPP) as the cross-linking agent. The characterization of the nanoparticle system included physical stability, particle size, polydispersity index (PdI), zeta potential, and morphological observation using a Transmission Electron Microscope (TEM). The freeze-dried powder was subsequently formulated into a nanosuspension, and its physical quality was evaluated. The results indicated a corrected extract yield of 26.65%. The selected nanoparticle formula (F4) exhibited an average particle size of 923.6 nm, a PdI of 0.606, and a zeta potential of +21.6 mV, demonstrating a spherical morphology but with a relatively broad particle size distribution. The evaluation of the nanosuspension over four weeks demonstrated a physically stable preparation with a pH range of 4.18–4.21, a specific gravity up to 1.0795 g/mL, and a 100% redispersion capability. In conclusion, the guava leaf extract was successfully prepared as a preliminary submicron particle formulation, demonstrating its potential to be further optimized and developed into a physicochemically stable nanosuspension.